2018
DOI: 10.1073/pnas.1816495115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of fusion pore formation driven by the neuronal SNARE complex

Abstract: Release of neurotransmitters from synaptic vesicles begins with a narrow fusion pore, the structure of which remains unresolved. To obtain a structural model of the fusion pore, we performed coarsegrained molecular dynamics simulations of fusion between a nanodisc and a planar bilayer bridged by four partially unzipped SNARE complexes. The simulations revealed that zipping of SNARE complexes pulls the polar C-terminal residues of the synaptobrevin 2 and syntaxin 1A transmembrane domains to form a hydrophilic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 56 publications
3
74
0
Order By: Relevance
“…These finding suggest that v-SNARE density (ND3 S , 0.022 syb2/nm 2 , ND3 L : 0.0042 syb2/nm 2 ) and not just copy number is a crucial parameter for pore formation. Indeed, a recent modeling study suggested that restricting the mobility of SNAREs, to increase their relative density, facilitates pore formation 25 . In sharp contrast, when syt1 was co-reconstituted into ND3 L , robust pore formation occurred upon addition of Ca 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These finding suggest that v-SNARE density (ND3 S , 0.022 syb2/nm 2 , ND3 L : 0.0042 syb2/nm 2 ) and not just copy number is a crucial parameter for pore formation. Indeed, a recent modeling study suggested that restricting the mobility of SNAREs, to increase their relative density, facilitates pore formation 25 . In sharp contrast, when syt1 was co-reconstituted into ND3 L , robust pore formation occurred upon addition of Ca 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Within this slice, lipids from the original stalk structure were maintained, and the remainder of the small vesicle was replaced with the large vesicle. This protocol was designed in analogy to that previously performed for nascent fusion pores (20). This hybrid stalk structure was then equilibrated using position restraints on 1) the phosphate groups of all lipids involved in the stalk, 2) the hemagglutinin fusion peptides, and 3) the hemagglutinin transmembrane domains.…”
Section: Supplementary Methodsmentioning
confidence: 99%
“…Additional details of the fusion pathway were resolved in simulations of SNARE mediated fusion between bilayers and nanodisks. 587 In the work of Pinot et al, 588 a combination of in vivo, in vitro, and in silico experiments were used to show the combined effect of lipids and proteins in shaping membranes during fission. In particular, the role of polyunsaturated lipids in membrane vesiculation by dynamin and endophilin was revealed.…”
Section: Increasing Complexitymentioning
confidence: 99%